A strategic shift from international to multinational banking: a “macro-developmental” paradigm of Japanese banks qua multinationals - OZAWA, T.; HINE, S. (PSL Quarterly Review, 2013)
During recent years the economics of technological change have developed new insights about the sources, forms and procedures of technological innovation. Three basic elements of technological innovation have been identified. Against this background, US and Italian experiences with technological change are examined. JEL: O31